(untitled) (Global Journal of Human-Social Science, 2012)
Societies have different culture, norms, values, customs, beliefs and attitudes towards fertility. In less developed countries people find high fertility as a defensive measure which is due to the low income level and economic roles and productive contribution of children. The present study has been designed to identify the effects of socio-economic and demographic factors on fertility behaviour the universe for the present study comprised rural and urban areas of Faisalabad. A sample of 160 respondents was collected from rural and urban by using simple random method. A well designed Interview Schedule was prepared for the collection of data. Thus the collected data were analyzed by appropriate statistical techniques. It was found a majority of the respondents 99.4 percent agreed that Pakistan population is increasing, majority of the respondents 76.3 percent had viewed to create awareness for fertility behaviour and majority of the respondents 63.8 percent had no family planning centre in their area. It was concluded majority of the respondents 56.3 percent had viewed that family planning is necessary for maternal and child health.